Applying AppSheet and Python for practical customs declaration training in the Logistics industry - Tran, Thị Cẩm Ly; Nguyen, Thị Phương Thư; Nguyen, Anh Tuấn (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
This article presents the integration of AppSheet and Python in teaching customs declaration procedures at universities. The goal is to improve the quality of education through modern technology. The methods include designing an AppSheet application development course and using Python programming to simulate real-world scenarios. The results showed significant improvements in student learning performance, with notable advantages over traditional teaching methods. Conclusion: Recommendations are made for broader application in education.